Evaluation of Cardiovascular Risk Factors in Women with Uterine Leimyoma: Is There a Link with Atherosclerosis? - Ebru Taştekin (Balkan Medical Journal, 2012)
Objective: Both uterine leimyoma (UL) and cardiovascular disease are public health problems affecting women at different age ranges. Smoking, obesity, and hypertension have been shown to be associated with UL in different random studies. However cardiovascular risk factors have not been evaluated systematically in patients with UL. Accordingly, we aimed to evaluate the cardiovascular risk factors and their relation with the presence of UL.Material and Methods: One hundred and eighty nine patients with the pathological diagnosis of UL and one hundred and eighty nine age matched control subjects without UL were retrospectively included in the study from our data base of the pathology and gynecology departments. Controls were patients with intact uteri who had visited the same physicians for a routine checkup that included a pelvic examination and uterine sonogram and without mention of physical findings consistent with UL. The following clinical and demographic parameters were recorded; age, sex, hypertension, diabetes mellitus, and hypercholesterolemia. Current cigarette smoking was defined as active smoking within the past 12 months. Results: Comparison of cardiovascular risk factors between with and without UL revealed that the presence of hypertension (80 (42.3%) vs 53 (28%) p=0.004) diabetes mellitus (33 (17.4%) vs. 16 (8.4%) p=0.009), smoking (31 (16.4%) vs. 11 (5.8%) p=0.001), were significantly higher in patients with UL than in control subjects. The mean-age and presence of hyperlipidemia were comparable between the two groups. Logistic regression analysis revealed an independent and positive association of UL with the presence of hypertension (odds ratio 2.02 CI: 1.25-3.27 p=0.004), diabetes mellitus (odds ratio 2.43 CI: 1.23-4.79 p=0.010), and smoking status (odds ratio 3.46 CI: 1.65-7.22 p=0.001).Conclusion: We have shown that major cardiovascular risk factors namely, hypertension, diabetes mellitus and smoking are significantly and independently associated with UL. Our findings highlight the possible association of UL with atherosclerosis.